Level of knowledge of bovine cattle producers about Aphthous Fever in the San Felipe Municipality of the Yaracuy state (Gaceta de Ciencias Veterinarias, 2017)
The present work is a descriptive study supported by non experimental field research, whose purpose is to determine the level of knowledge of bovine cattle producers about Aphthous Fever disease at San Felipe municipality, Yaracuy State. A questionnaire was used to data collection, with alternatives of polytomic responses as a measurement instrument, applied to a sample of 85 producers. A valuation table is established to determine the level of knowledge of the producers. It is concluded that the level of knowledge of the producers on basic aspects about Aphthous Fever disease was "Acceptable" and for prevention and control measures was "Regular".Comparing basic knowledge with training of Aphthous Fever producers, these were "Acceptable" for both groups (trained and untrained), while for knowledge on prevention and control, both were "Regular". The comparison between the basic knowledge of foot and mouth disease and the degree of academic education of the producers, the academic degree does not influence in this aspect, being "Acceptable" for all the degrees of academic instruction. While the comparison between knowledge on prevention and control measures with the degree of academic training of producers, was "Regular" for those of primary, high school, professional and none; for those of technical grade was "Acceptable".It is recommended to strengthen training and epidemiological surveillance, and implement this research in other states of the country.
Keywords: level of knowledge; Aphthous Fever; producers